2002
DOI: 10.3141/1809-15
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of Top-Down Cracks in Asphalt Pavements

Abstract: Top-down cracks (TDCs) in flexible and rubblized pavements constitute a distress that has been reported in the United States and other countries. Researchers have reached different conclusions regarding the causes of TDCs. In this study, field and laboratory investigations were conducted on conventional flexible and rubblized pavements exhibiting TDCs. The engineering characteristics of the pavement layers were obtained from the analysis of field data and laboratory test results. Detailed mechanistic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 4 publications
1
36
0
Order By: Relevance
“…Some considerations regarding the simulation: n Along with the concrete slab, it was chosen to simulate only the base layer. When simulating with or without the granular subbase layer, it was observed that the effect on the deflections was negligible; n The resilience modulus of the asphalt concrete base was based on the analyses of two studies that indicate a relatively high modulus to asphalt layers isolated (between two layers) because it is less exposed to thermal variations than the surface layer [15] [16]; n The values concerning the slab-base friction were set at 10 each, just to not let them null; again, in the simulations it was observed that a three-value variation on a scale of 1 to 100 does not cause significant changes in the deflection; n Regarding the slab thermal gradients, the temperature during the FWD test was 20 ° C on a very cloudy day. According to the equations developed during a thermal research in São Paulo, the thermal gradient between top and bottom should be of 7° [17].…”
Section: The Everfe Softwarementioning
confidence: 99%
“…Some considerations regarding the simulation: n Along with the concrete slab, it was chosen to simulate only the base layer. When simulating with or without the granular subbase layer, it was observed that the effect on the deflections was negligible; n The resilience modulus of the asphalt concrete base was based on the analyses of two studies that indicate a relatively high modulus to asphalt layers isolated (between two layers) because it is less exposed to thermal variations than the surface layer [15] [16]; n The values concerning the slab-base friction were set at 10 each, just to not let them null; again, in the simulations it was observed that a three-value variation on a scale of 1 to 100 does not cause significant changes in the deflection; n Regarding the slab thermal gradients, the temperature during the FWD test was 20 ° C on a very cloudy day. According to the equations developed during a thermal research in São Paulo, the thermal gradient between top and bottom should be of 7° [17].…”
Section: The Everfe Softwarementioning
confidence: 99%
“…For a single runway exit, the probability of aircraft passing over the cracked section given by Equation 10 simplifies to that of Equation 6. From the data in Tables 1 and 2, the probabilities λ m that the cracks at locations of y equal to 500 m, 1,000 m, and 1,750 m, respectively, are affected by the landings are computed to be 0.6333, 1, and 1, respectively.…”
Section: Analysis Of Failure Riskmentioning
confidence: 99%
“…Pavement research engineers have made significant efforts to obtain a better understanding of cracking mechanisms in pavements, with most studies focusing on crack initiation (Alkaissi and Khafagy, 2009;Gajewski and Sadowski, 2014) and crack propagation (Svasdisant et al, 2002;Wang et al, 2003) in pavements. Casey et al (2012) investigated the stress intensity factors of mode one and mode two cracking at the tip of a short crack and their influence on the continued propagation of cracks further into the pavement.…”
Section: Introductionmentioning
confidence: 99%